Navigating the choice: Family decision-making for elder care in urban Indonesia’s Panti Werdha - Julianti, Shinta; Munabari, Fahlesa (Universitas Trunojoyo Madura, 2024)
This study investigates the decision-making processes of upper-middle-class families in Jakarta, Indonesia, when choosing elder care facility (Panti Werdha) for their elderly parents. Utilizing the Rational Choice perspective, the research examines how these families navigate cultural and religious values while considering individual preferences and family dynamics. This qualitative case study explores the experiences of three families consisting of upper-middleclass families who have entrusted the care of their elderly relatives to Panti Werdha. It analyzes the negotiation stages among family members, particularly between children and their elderly parents. The study seeks to understand how these families balance material and moral considerations while adhering to societal norms, ultimately questioning whether their choices are truly rational. It reveals that the decision-making process is a complex negotiation involving rational choices, weighing material and moral benefits, and ultimately driven by the desire to minimize burdens and ensure the elderly's autonomy and well-being. The study identifies a shift in values among these families, suggesting that traditional models of family care are evolving, with nursing homes becoming a more acceptable option for the elderly and their families.